Assessment Criteria of Quality Activity of Staff Training in Higher Education Institutions - Khamrayeva Gulnoz Rustamovna (Scholars Digest Publishing, 2023)
This article describes the prospects of developing the skills of future specialists studying in the credit module system of a higher educational institution. In addition, the structure of improving the quality of the educational system was developed by the author as a model for organizing students' classes.
Keywords: Quality, element, material-technology, process, component, development, structure, credit module.